A review on the pesticides in coffee: Usage, health effects, detection, and mitigation - Merhi, Areej; Kordahi, Rita; Hassan, Hussein F. (Frontiers in Public Health, 2022)
Coffee is considered among the most popular beverages, and is classified as the second exported item worldwide. The presence of pesticides in this staple commodity is a challenge to import and export activities, in addition to the fact that pesticides are toxins of public health concern. Even if pesticides are applied properly and their residues are within the acceptable range, it is important to know the fate of these pesticides prior to their ingestion. A plethora of research has been done to optimize methods and thus to have valid procedures to test the presence of pesticides in coffee. In this review, the analytical methods used in these articles to detect and quantify the pesticides in coffee beans, roasted coffee, and coffee infusion were identified. This review highlights as well the main factors that play key role in having good separation, identification and recovery of pesticide residues in the aforementioned items. In addition, the review explains the effect of pesticides on human health and the mitigation techniques to the pesticides exposure.